Knowledge Externalities from Poverty Mapping in the European Union - World Bank Group (World Bank, Washington, DC, 2016)
The Poverty Mapping in the European Union (EU) project, an initiative of the World Bank and European Commission (EC) in cooperation with EU member states, has developed a set of high-resolution poverty maps by using information from recent national population censuses and household income surveys to estimate the rates of monetary poverty for small geographic areas in EU member states. This disaggregated information can help guide allocations of EU funds to the areas in highest need as well as inform decision making and policies at the national and sub -national levels in each of the EU member states. This brief outlines several of the key knowledge externalities gained in the context of this project that have improved the World Bank’s approach to poverty mapping, including methodological innovations in small area poverty estimation and enhancements to the publicly available poverty mapping software PovMap.